Improvement in Health-Related Quality of Life after Unilateral Total Knee Arthroplasty in Patients with Bilateral Knee Osteoarthritis. (December 2016) - Tan, Desmond Wei; Teh, Daniel Jing Wen; Razak, Hamid Rahmatullah Bin Abd; Tan, Andrew Hwee Chye
Purpose: To review the outcome of unilateral total knee arthroplasty (TKA) in patients with bilateral knee osteoarthritis (OA) to determine whether unilateral TKA can achieve good health-related quality of life (HRQoL). Methods: Records of 68 women and 25 men with severe bilateral knee OA who underwent unilateral TKA on the more symptomatic knee by a single surgeon and did not return for the second TKA within 2 years were reviewed. Outcome at 6 months and 2 years was assessed using the mental and physical component summary (MCS and PCS) of the Short-Form 36 (SF-36) for HRQoL as well as the Oxford Knee Score (OKS) and Knee Society Score (KSS) for knee-specific outcome. Results: The SF-36, OKS, and KSS improved significantly after unilateral TKA. Respectively for MCS and PCS of SF-36, OKS, and KSS knee and function scores, 65%, 89%, 98%, 98%, and 98% of patients reported absolute improvement at 2 years. Respectively for PCS, OKS, and KSS function score that a minimal clinically important difference (MCID) was established, 77%, 96%, and 80% of patients achieved MCID at 2 years. Conclusion: Unilateral TKA achieves good outcome in HRQoL at 2 years in patients with bilateral knee OA.